Review on Potassium Research in Sudan: Past, Present and Future Prospects (University of Khartoum Journal of Agricultural Sciences, 2022)
The objective of this review is to explore the possibility of changing the old perception among agriculturist from various disciplines that Sudanese soils are rich in potassium, this article reviewed the work that had been conducted on potassium in soils of Sudan since 1927.Hereby, potassium did not receive the worth attention in Sudan agricultural system. This article reviewed the work that had beenconducted on potassium in soils of Sudan since 1927. However, research work on soil potassium status and response of crops to the applied potassium is little. Early studies showed that some crops, like cotton and wheat, did not respond to the added potassium, however, sugarcane, banana, potato, and sweet potato crops responded well to the addedpotassium. Nevertheless, it is evident that application of potassium is a key factor in crops growth and quality. Accordingly, to improve crop production in Sudan, research for enhancing utilization of potassium element is needed. Many possible research for future directions have been suggested in the final part of this article.
Keywords: Potassium; Future Prospects; Sudan soils